10Kin1day: A Bottom-Up Neuroimaging Initiative - van den Heuvel, Martijn P.; Scholtens, Lianne H.; van der Burgh, Hannelore K.; Agosta, Federica; Alloza, Clara; Arango, Celso; Auyeung, Bonnie; Baron-Cohen, Simon; Basaia, Silvia; Benders, Manon J. N. L.; Beyer, Frauke; Booij, Linda; et al. (Frontiers in Neurology, 2019)
We organized 10Kin1day, a pop-up scientific event with the goal to bring together neuroimaging groups from around the world to jointly analyze 10,000+ existing MRI connectivity datasets during a 3-day workshop. In this report, we describe the motivation and principles of 10Kin1day, together with a public release of 8,000+ MRI connectome maps of the human brain.